La molteplicità e la crisi - Stefania Consigliere; Cristina Zavaroni (Archivio Antropologico Mediterraneo)
Managed in a way that both conceals and naturalizes postcolonial geopolitical violence, current migratory flows bring the anthropological field in our backyards, facing us with unprecedented forms of crisis both among migrants and among operators. It seems especially necessary to consider the actual possibility for persons to be built by means of multiple sets of attachments; and the ability to work implicit presuppositions, un-told and repressed events. The Bakonzo of the Rwenzori (Uganda), who are facing the intersection between the local anthropo-poietic logic and the one brought about by Euro-American “modernity”, make for and an excellent case study, allowing for an analogical comparison with what is happening here. The point is not to compare contents, but to be able to observe those dynamics that emerge in plural contexts. It may be concluded that multiplicity is not a risk factor in itself, rather, it acts as a multiplier of possibilities both in ordinary life and in critical times. The simultaneous presence of various sets of attachments proves problematic if one of the sets demands exclusivity.